How Best to Imagine: Comparing the Effectiveness of Physical Activity Imagery, Possible Self and Combined Interventions on Physical Activity and Related Outcomes. (March 2023) - Deck, Sarah; Semenchuk, Brittany; Hall, Craig; Duncan, Lindsay; Kullman, Sasha; Strachan, Shaelyn
Mental imagery and possible-selves interventions can help to improve physical activity (PA) in a variety of populations. Currently, no study has combined these two interventions to test the efficacy or possible synergistic effect. This study investigated the efficacy of a one-time exposure to one of three parallel interventions: imagery, possible selves, and combined, on exercise and self-efficacy, compared to a control group who were given nutritional information as an intervention. One hundred and twelve participants were randomized and provided data at three time points – eligibility screening, post-intervention, and 4-week follow-up. There were no significant group by time interactions or group differences. Main effects for time and exercise showed all participants increased in exercise suggesting that there are no advantages of the interventions. We discuss reasons why this may have occurred and suggest several areas for future researchers to expand upon, including replication with more exposure to interventions.